Study on empirical seismic codal guidelines for masonry buildings in Kollam, Kerala, India - Potty, N.S. (Taylor's University, 2015)
Masonry structures fail miserably due to lateral loads. Recent earthquakes in India and the world and the resulting losses highlighted the structural inadequacy of masonry buildings to seismic loads. Increase in frequency of earthquake in Kerala recently and increasing concern motivated the study. Localized survey at Kollam town in Kerala found that most of the structures were masonry. Kerala falls in Zones II and III. IS 13828 and IS 4326 provides masonry structures empirical design and construction features which may raise the earthquake resistance. The study is concerned with the numerical analysis of brick masonry walls (with and without seismic resistive features) subjected to dynamic loading with emphasis on their non-linear behaviour. Mechanical properties of three varieties of brick and three different mix proportion of mortar were determined. Using the material properties, nonlinear dynamic analysis of a masonry wall panel was done using ANSYS software and the ground motion record of Bhuj earthquake. The effect of size and position of openings in the masonry walls, the pier size, provision of lintels and the effect of mortar on resistance of walls under dynamic loads are discussed and possible retrofitting measures are suggested to strengthen the masonry brick wall. Â© 2015, School of Engineering, Taylorâs University.